(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
This article is about writing techniques used in teaching writing skills in foreign languages. It contains observations of improving writing skills. The objective of learning writing skill are students can communicate effectively in writing and developing skill in planning writing.